2021
DOI: 10.1039/d1sc03191k
|View full text |Cite
|
Sign up to set email alerts
|

Photoredox-mediated hydroalkylation and hydroarylation of functionalized olefins for DNA-encoded library synthesis

Abstract: DNA-encoded library (DEL) technology features a time- and cost-effective interrogation format for the discovery of therapeutic candidates in the pharmaceutical industry. To develop DEL platforms, the implementation of water-compatible transformations...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 120 publications
0
37
0
Order By: Relevance
“…To develop DELs platforms, on-DNA chemistries are required to incorporate multifunctional building-blocks from readily available chemicals under mild, dilute, and aqueous conditions. Recently, pioneering studies from the Baran, Flanagan, and Molander groups 20 have highlighted the power of radical-based reactivity for DELs synthesis through visible-light photochemistry 21 and RASS (reversible adsorption to solid support) technology. 22 N -(Acyloxy)phthalimides, 20 a ,21 d , f ,22 a amino acids, 20 b , c ,21 a , e carboxylic acids, 20 c 4-alkyldihydropyridines, 20 c silicates, 20 c alkyl halides, 21 b , c , f and α-TMS amines 21 c have all been employed as alkyl radical precursors.…”
Section: Resultsmentioning
confidence: 99%
“…To develop DELs platforms, on-DNA chemistries are required to incorporate multifunctional building-blocks from readily available chemicals under mild, dilute, and aqueous conditions. Recently, pioneering studies from the Baran, Flanagan, and Molander groups 20 have highlighted the power of radical-based reactivity for DELs synthesis through visible-light photochemistry 21 and RASS (reversible adsorption to solid support) technology. 22 N -(Acyloxy)phthalimides, 20 a ,21 d , f ,22 a amino acids, 20 b , c ,21 a , e carboxylic acids, 20 c 4-alkyldihydropyridines, 20 c silicates, 20 c alkyl halides, 21 b , c , f and α-TMS amines 21 c have all been employed as alkyl radical precursors.…”
Section: Resultsmentioning
confidence: 99%
“…The independent absorption spectra of 2-alkenylpyridine 1a , ( R )-TRIP, and RAE 2a in THF showed absorption exclusively in the ultraviolet region, whereas HE ( HE-1 ) was found to absorb in the visible region (Figure a,b). However, a mixed solution of RAE and HE displayed a significant bathochromic shift in absorbance, which suggested that a new molecular aggregation (Figure b) might be generated between electron-deficient RAEs and electron-rich HE, proving a plausible EDA complex formation prior to SET events. Interestingly, the addition of ( R )-TRIP to a solution of RAE and HE resulted in a further bathochromic shift, and the absorption enhancement was also observed with increasing concentrations of ( R )-TRIP (Figure S1D in the Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…To improve the three-dimensionality and physicochemical properties of lead compounds, drug discovery chemists have long endeavored to replace the venerable arene ring in an effort to “escape from flatland”. , Thus, arene bioisosteres such as bicyclo[1.1.1]­pentanes (BCPs), bicyclo[2.2.2]­octanes, or cubanes have been of interest to the synthesis community. , Recent advances include efficient preparations of diversely substituted BCPs, or the Giese-type additions of non-stabilized BCP radical intermediates to alkene coupling partners, delivering sp 3 -rich products . Likewise, the ability to install arene bioisosteres on-DNA is of significant interest to the DEL field, but there exist only a few examples under DNA-compatible reaction conditions. In 2018, Baran and coworkers applied a bicyclo[2.2.2]­octane N -hydroxyphthalimide (NHPI) redox active ester in an on-DNA Giese reaction with zinc nanopowder as a reductant, but BCP or cubane examples were not included. To the best of our knowledge, there has only been one example of a BCP radical addition on-DNA, likely because of the difficulty of generating the corresponding non-stabilized radical intermediate .…”
Section: Introductionmentioning
confidence: 99%